Estereótipos e mulheres na cultura marroquina - Sadiqi, Fatima (2016)
Estereótipos sobre as mulheres no Marrocos podem ser caracterizados como crenças culturais incompletas e inexatas mantidas por algumas pessoas e que se encontram inscritos em expressões lingüísticas ou em discursos subliminares. A cultura popular marroquina emprega representações poderosas para transmitir e sustentar tais estereótipos. Embora existam alguns estereótipos positivos, a maioria dos estereótipos sobre as mulheres no Marrocos é negativa e reflete ditames patriarcais subliminares que estruturam as relações de gênero nas culturas marroquinas. As mulheres marroquinas, no entanto, não são receptoras e transmissoras passivas, mas usam estratégias para lutar contra esses estereótipos.Abstract Stereotypes about women in Morocco may be characterized as incomplete and inaccurate cultural beliefs that some people hold about them and that are encoded in linguistic expressions as well as in underlying discourses. Popular Moroccan culture employs powerful representations to transmit and sustain these stereotypes. Although there are some positive stereotypes, most stereotypes about women in Morocco are negative and reflect the underlying patriarchal dictates that structure gender relations in Moroccan cultures. Moroccan women are not, however, passive recipients and carriers of stereotypes; they use strategies to fight back.Key Words: Gender, Women, Stereotypes, Moroccan Culture